No Evidence of Myocardial Oxygen Deprivation in Nonischemic Heart Failure. (November 2015) - Dass, Sairia; Holloway, Cameron J.; Cochlin, Lowri E.; Rider, Oliver J.; Mahmod, Masliza; Robson, Matthew; Sever, Emily; Clarke, Kieran; Watkins, Hugh; Ashrafian, Houman; Karamitsos, Theodoros D.; Neubauer, Stefan
Abstract : Background—: Whether the myocardium in nonischemic heart failure experiences oxygen limitation remains a long-standing controversy. We addressed this question in patients with dilated cardiomyopathy (DCM) using a dual approach. First, we tested the changes in myocardial oxygenation between rest and stress states, using oxygenation-sensitive cardiovascular magnetic resonance. Second, we sought to assess the functional consequences of oxygen limitation at rest by measuring myocardial energetics before and after short-term oxygen supplementation. Methods and Results—: Twenty-six subjects (14 DCM and 12 normal) underwent cardiac magnetic resonance imaging at 3 Tesla to assess cardiac volumes, function, oxygenation, and first-pass perfusion (0.03 mmol/kg Gd-DTPA bolus) at stress and rest (4–6 minutes IV adenosine, 140 μg/kg per minute). Signal intensity change (SIΔ) and myocardial perfusion reserve index (MPRI) were measured from oxygenation and perfusion images, respectively. Furthermore, the effect of oxygen supplementation on resting myocardial energy metabolism was tested using 31 P MR spectroscopy, measuring PCr/ATP ratios in both groups at baseline and after 4 hours of oxygen via facemask in the DCM group. During stress, there were equivalent rises in rate pressure product in both groups (DCM, 76±15% and normal, 79±9%; P =0.84). MPRI was significantly reduced in DCM (1.51±0.11 versus normal 1.86±0.10; P =0.03). However, there was no difference in oxygenation between groups: SIΔ in DCM 17±3% versus normal 20±2% ( P =0.38). Furthermore, at a left ventricular segmental level, there was no correlation between oxygenation-sensitive SIΔ and MPRI ( R =0.06; P =0.43). Resting PCr/ATP was reduced in DCM (1.66±0.07 versus normal 2.12±0.06; P =0.002). With oxygen supplementation, there was no change in PCr/ATP (1.61±0.08; P =0.58; Δ=0.04±0.05). There was also no effect of oxygen on systolic function (ejection fraction pre oxygen, 34±1%; post oxygen, 36±2%; P =0.46; Δ 2±1%). Conclusions—: Our results demonstrate dissociation between microvascular dysfunction and oxygenation in DCM, suggesting that the impairment of perfusion is not sufficient to cause deoxygenation during stress. Cardiac energetics are unaffected by oxygen supplementation, indicating the absence of relevant myocardial hypoxia at rest. Our study suggests that novel treatments for nonischemic heart failure should focus on efforts to directly target cardiomyocyte function and metabolism rather than oxygen delivery and microvascular function.